Nelson textbook of pediatrics - Robert M Kliegman (Elsevier/Saunders, 2011)
Nelson Textbook of Pediatrics has been the world's most trusted pediatrics resource for nearly 75 years. Drs. Robert Kliegman, Bonita Stanton, Richard Behrman, and two new editors-Drs. Joseph St. Geme and Nina Schor-continue to provide the most authoritative coverage of the best approaches to care. This streamlined new edition covers the latest on genetics, neurology, infectious disease, melamine poisoning, sexual identity and adolescent homosexuality, psychosis associated with epilepsy, and more. Best of all, the expanded online access at www.expertconsult.com features the full text, case studies, new references and journal articles, Clinics articles, and exclusive web-only content so that you get even more out of this invaluable reference.